2022
DOI: 10.3390/f13060896
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Functional Structure of Wood Communities among Different Disturbance Regimes in a Temperate Mountain Forest

Abstract: The mechanisms responsible for biodiversity formation and maintenance are central themes in biodiversity conservation. However, the relationships between community assembly, phylogeny, and functional traits remain poorly understood, especially following disturbance. In this study, we examined forest community assembly mechanisms in different disturbance regimes across spatial scales and including tree life history classes, using phylogenetic and functional trait metrics. Across disturbance regimes, phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…There were some negative values of SES.PD_Dpw in the 2010s, indicating that the phylogenetic change between the lakes was slower than expected, but this trend was not dominant. Some studies have shown that fish and other groups that have not been disturbed by human activities (e.g., the blockage of rivers and lakes, and overfishing) are prone to form a phylogenetically overdispersion structure, as the evolutionary history of this area is old and the contemporary environment is more stable (Ashford et al, 2018; Li et al, 2022). The interaction between organisms makes the evolutionary relationship and kinship more distant, and species that use food resources in different niche spaces can coexist (Kooyman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There were some negative values of SES.PD_Dpw in the 2010s, indicating that the phylogenetic change between the lakes was slower than expected, but this trend was not dominant. Some studies have shown that fish and other groups that have not been disturbed by human activities (e.g., the blockage of rivers and lakes, and overfishing) are prone to form a phylogenetically overdispersion structure, as the evolutionary history of this area is old and the contemporary environment is more stable (Ashford et al, 2018; Li et al, 2022). The interaction between organisms makes the evolutionary relationship and kinship more distant, and species that use food resources in different niche spaces can coexist (Kooyman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%